2022
DOI: 10.1038/s41598-022-20516-w
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of SARS-CoV-2 viral load across different altitudes

Abstract: SARS-CoV-2 has spread throughout the world, including areas located at high or very high altitudes. There is a debate about the role of high altitude hypoxia on viral transmission, incidence, and COVID-19 related mortality. This is the first comparison of SARS-CoV-2 viral load across elevations ranging from 0 to 4300 m. To describe the SARS-CoV-2 viral load across samples coming from 62 cities located at low, moderate, high, and very high altitudes in Ecuador. An observational analysis of viral loads among nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The COVID-19 pandemic that began in December 2019 remains a serious threat to public health. Previous studies have reported that SARS-CoV-2 infection and COVID-19related mortality rates are lower in populations residing in high-altitude, as compared to low-altitude regions [10,15,16], which may be related to the physiological capacity to tolerate hypoxia, high UV exposure, and lower atmospheric pressure [8,[17][18][19]. Tolerance to long-term hypoxia of populations residing in high-altitude environments leads to increased molecular levels of hypoxia-inducible factor 1α and 2α, which trigger adaptive responses to hypoxic conditions and attenuation of acute respiratory illnesses [20][21][22].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The COVID-19 pandemic that began in December 2019 remains a serious threat to public health. Previous studies have reported that SARS-CoV-2 infection and COVID-19related mortality rates are lower in populations residing in high-altitude, as compared to low-altitude regions [10,15,16], which may be related to the physiological capacity to tolerate hypoxia, high UV exposure, and lower atmospheric pressure [8,[17][18][19]. Tolerance to long-term hypoxia of populations residing in high-altitude environments leads to increased molecular levels of hypoxia-inducible factor 1α and 2α, which trigger adaptive responses to hypoxic conditions and attenuation of acute respiratory illnesses [20][21][22].…”
Section: Discussionmentioning
confidence: 90%
“…COVID-19 spread to almost all provinces of China after first detected in the city of Wuhan [6,7]. Before August 2022, there were relatively few cases of COVID-19 in the mountainous Tibetan Autonomous Region, which may be associated with high-altitude hypoxia, exposure to ultraviolet light (UV), and low atmospheric pressure [8][9][10][11]. However, the sudden outbreak of COVID-19 throughout the Tibetan Plateau after July 2022 contradicts the notion that Tibet has been exempt from COVID-19 for the past 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a novel analysis to investigate the incidence and mortality of CD at different altitudes. Ecuador’s unique topography, with 221 cities situated at varying elevations ranging from sea level to 4,300 m, provides an exceptional opportunity to study the burden of diseases at different altitudes ( 39 41 ). Our study found that the majority of CD cases ( n = 107) were concentrated at elevations below 2,500 m. To provide a more nuanced analysis, we also employed the International Society of Mountain Medicine classification, which classifies altitudes into different categories, and observed that the highest incidence and mortality rates were found at low and moderate altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…However, other conditions typical of high altitude, such as radiation and air humidity, must also be considered as variables of the protective role [ 37 ]. A study conducted in Ecuador did not find a lower viral load related to altitude perhaps because they did not consider the time of development of the disease or the peak of the viral load, the state of the immune system or the use of medication that can reduce the viral load [ 45 ].…”
Section: Discussionmentioning
confidence: 99%